Dominance of Methicillin-Resistant Staphylococcus aureus in a Japanese Infant with Recessive Dystrophic Epidermolysis Bullosa - Makoto Kondo; Shota Takashima; Hiroyuki Goto; Koji Habe; Ken Natsuga; Keiichi Yamanaka (Karger Publishers, 2021)
A male infant had the very fragile skin and easily formed bullas by rubbing and scratching from his birth. He was diagnosed with severe recessive dystrophic epidermolysis bullosa (RDEB) due to the lack of type VII collagen by performing an immunofluorescence mapping method from a skin biopsy specimen of the patient's bulla. We analyzed the skin microbiome using next-generation sequencer. The species from the patient's skin revealed the dominance of Staphylococcus aureus (S. aureus) similar to the reports from Austria and Chile severe RDEB patients, and these results are same as the pattern isolated from the skin of atopic dermatitis (AD) patients with flares. The interaction of microbiome and skin microenvironment may be similar between RDEB and AD worldwide.